2016
DOI: 10.1371/journal.pone.0165453
|View full text |Cite
|
Sign up to set email alerts
|

The High Level of Aberrant Splicing of ISCU in Slow-Twitch Muscle May Involve the Splicing Factor SRSF3

Abstract: Hereditary myopathy with lactic acidosis (HML) is an autosomal recessive disease caused by an intronic one-base mutation in the iron-sulfur cluster assembly (ISCU) gene, resulting in aberrant splicing. The incorrectly spliced transcripts contain a 100 or 86 bp intron sequence encoding a non-functional ISCU protein, which leads to defects in several Fe-S containing proteins in the respiratory chain and the TCA cycle. The symptoms in HML are restricted to skeletal muscle, and it has been proposed that this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It was therefore suggested that PTBP1 can act as a repressor of the incorrect splicing of ISCU (Nordin et al., ). In a recent study, we showed that the levels of incorrectly spliced ISCU vary among a number of mouse tissues, where the highest level of incorrect splicing was observed in the slow fiber muscle soleus (Rawcliffe et al., ). In this study, we examined the same tissues for levels of Ptbp1 RNA and protein to see whether there was a correlation between the levels of ISCU mis‐splicing and the levels of Ptbp1 (Figure a,b).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…It was therefore suggested that PTBP1 can act as a repressor of the incorrect splicing of ISCU (Nordin et al., ). In a recent study, we showed that the levels of incorrectly spliced ISCU vary among a number of mouse tissues, where the highest level of incorrect splicing was observed in the slow fiber muscle soleus (Rawcliffe et al., ). In this study, we examined the same tissues for levels of Ptbp1 RNA and protein to see whether there was a correlation between the levels of ISCU mis‐splicing and the levels of Ptbp1 (Figure a,b).…”
Section: Resultsmentioning
confidence: 98%
“…ISCU transgenic mice (Rawcliffe et al., ) from a CBA/B6 background were kept in standard cages with free access to water and food (CRM Expanded, SDS). Mice of both genders were sacrificed by cervical dislocation at 9 weeks of age, and the organs of interest were collected and immediately frozen in N 2 (l) followed by storage in −80°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations